The correlation between mannanase and cellulase activities towards fibre content of palm oil sludge fermented with Aspergillus niger - Purwadaria, T.; Sinurat, A.P.; Haryati, T.; Sutikno, I.; ., Supriyati; Dharma, J. (Indonesian Animal Sciences Society, 1998)
Enzyme (mannanase and cellulase) activities and fibre (hemicellulose, cellulose and lignin) contents were determined during the fermentation course of palm oil sludge with Aspergillus niger TL (wild type) and A. niger ES I (an asporogenous mutant). The analyses were carried out at the incubation time of 3 and 4 days of aerobic fennentation and at 2 days of anaerobic fermentation afterward. The correlations between mamlanase activity with hemicellulose content and cellulose activity with cellulose content were calculated by linear regression . The activities of matutanase and cellulase are increasing during the aerobic fennentation, while in the anaerobic fennentation the enzyme activities are decreasing due to instability of the enzymes. The enzyme activities of ESI are higher than the TL. The regression coefficient is highly significant for correlation between mamlanase and hemicellulose content of fermented product by ESI (r = 0.83; P<0.01) . While other correlations are not statistically significant (P>0 .05) . Marutanase and cellulase activities were also detected after the fermented product dried at 60Â°C which indicated the enzymes are quite stable . Key words: Palm oil sludge, fermentation, cellulase, mamlanase, cellulose, hemicellulose, Aspergillus niger